1995
DOI: 10.1002/ana.410370311
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography and magnetic resonance spectroscopy of cerebral glycolysis in children with congenital lactic acidosis

Abstract: Congenital lactic acidosis with neurological symptoms may be due to a variety of disorders of energy metabolism. We investigated whether positron emission tomography (PET) and proton magnetic resonance spectroscopy ('H MRS) are capable of demonstrating specific changes to facilitate diagnosis. A corresponding increase of cerebral lactate (with MRS) and rate of glycolysis (with PET) was observed in 2 children with biochemical evidence of defective mitochon drial respiration. No such increase was noted in a chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Coregistration of image data from the different modalities has indicated the value of such comparative studies in stroke [27], gliomas [28], and degenerative [29] and congenital or hereditary disorders [30]. However, coregistration was limited since it required multiple investigations in different laboratories.…”
Section: Real-time Imaging Of Complementary Informationmentioning
confidence: 99%
“…Coregistration of image data from the different modalities has indicated the value of such comparative studies in stroke [27], gliomas [28], and degenerative [29] and congenital or hereditary disorders [30]. However, coregistration was limited since it required multiple investigations in different laboratories.…”
Section: Real-time Imaging Of Complementary Informationmentioning
confidence: 99%
“…One might predict a steady-state increase in anaerobic glycolysis (in astrocytes or also in neurons?) if such closed-loop adaptations are insufficient to normalise oxidative ATP synthesis; there have been case reports in mitochondrial encephalopathy of increased cerebral lactate by 1 H-MRS [120,121], and PET evidence of increased glycolysis [120,122] and decreased CMR O 2 [122]. However, in the mo(vbr) mouse, in which cytochrome oxidase and Complex I are decreased, there is no 31 P-MRS abnormality in vivo apart from raised pH (of unknown cause) [123], because the control properties of the respiratory chain alter so that flux is preserved [124] -in short, there is spare capacity.…”
Section: Chronic Impairment Of Mitochondrial Functionmentioning
confidence: 99%
“…When Bolter and Chefurka (35) added myxothiazol, a tight inhibitor of mitochondrial complex III, to mouse liver, they found that it mimicked reductive stress and significantly increased hydrogen peroxide production. It should be noted that inherited respiratory chain disorders were documented in humans (36).…”
Section: Other Issuesmentioning
confidence: 99%